Youth Homicide: A Review of the Literature and a Blueprint for Action - Heide, Kathleen M. (International journal of offender therapy and comparative criminology, 2003)
This article first synthesizes the literature on clinical and empirical findings related to youth homicide. Thereafter, it reviews the literature with respect to the treatment of juvenile homicide offenders. Although a large body of literature exists, many questions regarding etiology, associated risk factors, intervention strategies, and long-term outcomes remain unanswered. The article concludes with recommendations to guide future research efforts with the aim of increasing understanding of etiological factors associated with juvenile homicide and designing effective intervention strategies. Greater advances in knowledge will follow with the implementation of enhanced methodological designs that examine juvenile homicide across four distinct time frames: the years preceding the homicide, the time period immediately following the homicide, the incarcerative or treatment period, and the postrelease period